From immediate community to imagined community: Social identity and the co-viewing of media event. Issue 4 (December 2016) - Cui, Xi; Rui, Jian; Su, Fanbo
This study examines how different types of co-viewing are associated with viewers' emotional response to the live broadcast of media events and their social identity. A survey ( N  = 206) was conducted to examine the effect of the live broadcast of a grand national ceremony in China. Results show that viewers experienced emotional arousal when they watched the media event in physical, mediated, and perceived co-viewing conditions. Among these conditions, mediated co-viewing, operationalized as social media engagement during the event, is the strongest predictor of emotional arousal. Moreover, emotional arousal fully mediates the relationship between co-viewing conditions and viewers' national identity conveyed in the broadcast ceremony. With empirical evidence, we demonstrate the continued relevance of the genre of media events and the importance of co-viewing experiences in the contemporary media ecology. We argue that this broadcast genre is still effective with regard to social integration, and dual-screening media events could be a new mechanism of this effect.